Association between the methylenetetrahydrofolate reductase C677T polymorphism and hepatocellular carcinoma risk: a meta-analysis - Shen Xi-Zhong; Qu Li-Shuai; Jin Fei (BMC, 2009)
Abstract Background Methylenetetrahydrofolate reductase (MTHFR) is a key enzyme in the metabolism of folate. The non-synonymous single nucleotide polymorphism (nsSNP), C677T (Ala>Val, rs1801133), has been verified to impair enzyme activity. The association with cancer susceptibility, including hepatocellular carcinoma (HCC), has also been widely studied. The results, however, were inconsistent. To shed light on the influence of MTHFR C677T polymorphism on HCC, a meta-analysis was conducted. Methods The meta-analysis of C677T consisted of 10 studies (1814 cases/2862 controls). The association was measured by using random-effect (RE) or fixed-effect (FE) odds ratio (OR) combined with 95% confidence intervals (CIs) according to the studies' heterogeneity. Results Using genetic model analysis, C677T polymorphism was found to increase the risk of HCC in a complete overdominant model, which indicates that heterozygotes CT are at a lesser risk of HCC than either homozygotes CC or TT. Meta-analyses of the 10 studies showed that the TT genotype increased the risk of HCC as compared to the CT genotype: FE OR was 1.20 (95%CI: 1.00-1.45, p for heterogeneity = 0.21). When subgroup analysis was done between the HCC cases and the chronic liver disease (CLD) patients of four studies, meta-analysis showed that individuals with the TT genotype had increased HCC risk compared with those with the CT genotype: FE OR (TT vs. CT) reached 1.81 (1.22-2.71, p for heterogeneity = 0.25). Meanwhile, the C677T polymorphism also increased HCC risk in a recessive model when cases were compared to CLD patients of four studies: RE OR reached 1.85 (95%CI: 1.00-3.42, p for heterogeneity = 0.06). Overall, there was some extent heterogeneity when analyses were performed in various models. There was no publication bias. Conclusion MTHFR C677T polymorphism increased the risk of HCC in an overdominant model, and might be a risk factor for HCC occurrence, especially in CLD patients. The association warranted further studies.